Research on the Hot Rolling of Blanks on Oval and Circle Dies - I. Zolotukhin, P; M. Volodin, I; I. Volodin, A (International Journal of Engineering and Technology, 2018)
The results of the blanks hot rolling modeling in the «QForm 3D» program and the research on the deformed shape (DS) of metal by grid method are presented. Comparison of data obtained by different methods is made when analyzing the rolling of blanks for two passes using the circle-oval-circle scheme.